2021
DOI: 10.1038/s41390-021-01653-w
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention during pediatric resuscitation with feedback devices: a randomized simulation study

Abstract: Background The aim of this study was to investigate the effect of feedback devices on visual attention and the quality of pediatric resuscitation. Methods This was a randomized cross-over simulation study at the Medical University of Vienna. Participants were students and neonatal providers performing four resuscitation scenarios with the support of feedback devices randomized. The primary outcome was the quality of resuscitation. Secondary outcomes were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 40 publications
0
18
1
Order By: Relevance
“…It is the responsibility of both the individual healthcare professional, educational institutions and the NICU leadership that knowledge of and skills in providing safe and effective ventilation are repeatedly trained and tested. The results from this study contrast with studies that found that training with real-time feedback improved ventilation performance ( 10 , 14 ), and in the following we discuss potential causes for this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It is the responsibility of both the individual healthcare professional, educational institutions and the NICU leadership that knowledge of and skills in providing safe and effective ventilation are repeatedly trained and tested. The results from this study contrast with studies that found that training with real-time feedback improved ventilation performance ( 10 , 14 ), and in the following we discuss potential causes for this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…In previous studies, results from real-time feedback have either been masked or made visible to the participants during ventilation ( 10 , 14 ). In this study, the participants trained their ventilation skills with visible real-time feedback, followed by a simulation without visible feedback.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies should assess long-term neurodevelopmental outcomes. Studies are also required to determine whether an RFM adds to the attentional and cognitive demands on healthcare providers or diverts attention away from the infant 40–44. It is unclear whether specialised training is required to maximise the benefit of an RFM 43…”
Section: Discussionmentioning
confidence: 99%